Digital Skills : Frameworks and Programs - Bashir, Sajitha (World Bank, Washington, DC, 2021)
Digital skills constitute one of the five foundational pillars of the Digital Economy for Africa (DE4A) initiative, launched by the World Bank, and are needed to mobilize digital innovations to transform economies, societies and governments in Africa. The other foundational pillars are digital infrastructure, digital platforms, digital financial services and digital entrepreneurship. African economies require both a digitally competent workforce as well as digitally literate citizens who could reap the benefits that the digital society brings. This paper presents a framework for digital skills, based on a review of international frameworks. It discusses the demand and supply of digital skills as well as a mapping with formal education programs at different levels of the system that could produce these skills. It also gives examples of programs outside of formal education programs that could be used for imparting skills training. Finally, it suggests indicators that could be used to better measure progress towards the objectives of the DE4A initiative.